The Impact of Teachers’ Classroom Management Skills on Self-Efficacy of Students - Dr. Bushra Salahuddin; Sultan Akbar Shah; Dr. Fahmida Bibi (Journal of Religion and Society, 2026)
The importance of effective classroom management skills in promoting positive student outcomes is highly established but little is known on the way it affects the psychological beliefs of students especially self-efficacy as it is not well explored in the Pakistani educational setting. The research problem was use of classroom management practices by teachers in self-efficacy of learners in the District of D.I. Khan, Khyber Pakhtunkhwa, Pakistan, in the public secondary schools. Three purposes guided the study, namely, to investigate the levels of classroom management of the teachers and the self-efficacy of the students, to establish the connection between the two variables, and to find out how the classroom management affects the self-efficacy of the students. Quantitative research approach was used and it was descriptive. The sample size was 80 male heads of the public secondary schools in District D.I. Khan and the entire population was used as the sample according to the defining sampling criteria set out by LR Gay (2003). Data were gathered on the basis of a structured questionnaire including 5-point Likert scale and processed with the help of descriptive statistics (mean, Standard deviation), Pearson Product-Moment Correlation, and Linear Regression Analysis with the help of SPSS software. The results have shown that classroom management (M = 3.08, SD = 1.31) by teachers and self-efficacy (M = 3.25, SD = 1.28) by students were rated as moderately positive, and a significant portion of the respondents had the undecided opinions. The null hypothesis was rejected because the correlation between classroom management and self-efficacy (r = 0.45, p < 0.05) was found to be significant and positive. Moreover, the regression analysis showed that classroom management was very important in predicting self-efficacy among students, who attributed 20.3% of the variance (R 2 = .203) to classroom management. The researchers conclude that positive classroom management is correlated and significantly predictive of increased student self-efficacy. It is suggested that teacher professional development initiatives in the area should focus more on evidence-based strategies of classroom management and that research should be conducted in the future to examine other variables that lead to student self-efficacy. Keywords: Classroom Management, Self-Efficacy, Secondary School Heads, Quantitative Research, D.I. Khan, Pakistan https://doi.org/10.5281/zenodo.18651644